2017
DOI: 10.3390/coatings7020026
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhanced Raman Scattering Substrates Made by Oblique Angle Deposition: Methods and Applications

Abstract: Surface Enhanced Raman Spectroscopy presents a rapid, non-destructive method to identify chemical and biological samples with up to single molecule sensitivity. Since its discovery in 1974, the technique has become an intense field of interdisciplinary research, typically generating >2000 publications per year since 2011. The technique relies on the localised surface plasmon resonance phenomenon, where incident light can couple with plasmons at the interface that result in the generation of an intense electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Physical vapor deposition (PVD) is an important family of techniques for thin film processes. Applications of PVD deposited thin films include: optical band-pass filters [1], surface enhanced Raman spectroscopy [2], hydrophobic coatings, and sensors [3]. PVD involves the conversion of a source material into the gas phase, which is then deposited onto a substrate surface [4] and can be achieved through either evaporation or sputtering [5].…”
Section: Introductionmentioning
confidence: 99%
“…Physical vapor deposition (PVD) is an important family of techniques for thin film processes. Applications of PVD deposited thin films include: optical band-pass filters [1], surface enhanced Raman spectroscopy [2], hydrophobic coatings, and sensors [3]. PVD involves the conversion of a source material into the gas phase, which is then deposited onto a substrate surface [4] and can be achieved through either evaporation or sputtering [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other groups had optimized the performance of AgNRs substrate by adjusting the process parameters [44,45,46]. In recent years, more methods based on OAD have been investigated to fabricate novel SERS substrate for improving SERS performance, reducing costs, etc [47]. Singh et al demonstrated that if AgNRs grew at 140 K, it would get the same length of nanorods as those done at room temperature in a lower deposition time and show greater SERS performance than the substrate made at room temperature [48].…”
Section: Introductionmentioning
confidence: 99%
“…However, Oh et al got the opposite conclusion that substrates made at higher temperatures had higher SERS enhancements [49]. There is little in the literature that studies this temperature dependence with other nanostructures, such as AuNRs; perhaps this will be a new area that will be expanded on in the near future for higher SERS performance [47]. For fabrication into smaller dimensions with better control, template assisted deposition was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithography-based sputtering is convenient for fabricating nanostructured SERS substrate, but it requires a lot of money and time. In recent years, research has been reported on obtaining a nanorod-structured SERS substrate by simply tilting the substrate during sputtering [22,23,24]. In this way, SERS substrates can be fabricated at a lower cost in a shorter time than other methods.…”
Section: Introductionmentioning
confidence: 99%